My First Encyclopedia: Our Planet Earth (Kingfisher Publications Plc, 2000)
Exciting and wide-ranging, this introduction to our planet investigates everything from earthquakes and volcanoes to waterfalls and storms.
Keywords: Facts / Encyclopedia / Earth